Changes in Autonomic Tone in Premature Infants Developing Necrotizing Enterocolitis - Al-Shargabi, Tareq; Reich, Daniel; Govindan, R. B.; Shankar, Somya; Metzler, Marina; Cristante, Caitlin; McCarter, Robert; Sandler, Anthony D.; Said, Mariam; Plessis, Adre du (American Journal of Perinatology, 2018)
Background Necrotizing enterocolitis (NEC) is a complication of prematurity with a high mortality rate. Currently, there are no reliable biomarkers capable of identifying infants at risk for developing NEC. We sought to determine the autonomic nervous system antecedents of NEC in premature infants, using heart rate variability (HRV).Materials and Methods HRV was quantified by retrieving archived electrocardiogram (EKG) data from 30 premature infants from 4 days prior, through 4 days after, the clinical NEC diagnosis. HRV metrics were compared with those on the diagnosis day using the receiver operating characteristic (ROC) analysis.Results HRV metrics showed a depression of autonomic tone that preceded the clinical NEC diagnosis by 2 days, and which recovered to baseline by 2 days after diagnosis (area under the curve [AUC] < 0.7). The pattern of HRV change was significantly associated with the clinical severity of NEC (stage II vs. stage III).Conclusion Our studies suggest that readily accessible metrics of autonomic depression might expedite the diagnosis of NEC and its severity in a clinically meaningful manner. Clearly, these studies need to be extended prospectively to determine the diagnostic utility of this approach.
Keywords: preemie; heart rate variability; autonomic nervous system; necrotizing enterocolitis